2006
DOI: 10.1128/aem.72.2.1542-1550.2006
|View full text |Cite
|
Sign up to set email alerts
|

Induction by Klebsiella aerogenes of a Melanin-Like Pigment in Cryptococcus neoformans

Abstract: While studying the interaction of Cryptococcus neoformans with Dictyostelium discoideum, we noticed that yeast colonies in agar with a feeder lawn of Klebsiella aerogenes were brown. This finding was intriguing because C. neoformans colonies are not pigmented unless they are provided with precursors for melanization. Strains of all C. neoformans serotypes produced brown pigment in response to K. aerogenes at 22, 30, and 37°C. Pigment production required fungal laccase and was suppressed by high concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 23 publications
1
50
0
1
Order By: Relevance
“…These include several catecholamines, such as methyl-DOPA and norepinephrine (Garcia-Rivera et al, 2005). In addition, C. neoformans can use substrates produced by bacteria for melanization (Frases et al, 2006(Frases et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include several catecholamines, such as methyl-DOPA and norepinephrine (Garcia-Rivera et al, 2005). In addition, C. neoformans can use substrates produced by bacteria for melanization (Frases et al, 2006(Frases et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…C. neoformans presumably melanizes during mammalian infection by scavenging substrates from tissue that remain unidentified (Rosas et al, 2000a). Recent reports have enumerated an expanded list of substrates that can be used for melanization in vitro, and these include several bacterial products (Frases et al, 2006(Frases et al, , 2007Garcia-Rivera et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in cheese ripening, the interaction between Kluyveromyces lactis and Brevibacterium linens results in an altered profile of aromatic volatile sulfur compounds, which is believed to be due to the supply of an important precursor molecule, methanethiol, by the bacterium to the yeast (10). Another example of such anabolism is the synthesis of melanin pigments during the Klebsiella aerogenesCryptococcus neoformans BFI (114,115). C. neoformans is able to use homogentisic acid produced by K. aerogenes as a precursor for the synthesis of melanin pigments that enhance the virulence of the fungus and afford it protection against UV and other environmental stresses (114,115).…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…Another example of such anabolism is the synthesis of melanin pigments during the Klebsiella aerogenesCryptococcus neoformans BFI (114,115). C. neoformans is able to use homogentisic acid produced by K. aerogenes as a precursor for the synthesis of melanin pigments that enhance the virulence of the fungus and afford it protection against UV and other environmental stresses (114,115). A less beneficial conversion of a bacterial metabolite occurs upon coculturing of P. aeruginosa and C. albicans, since a pyocyanin precursor produced by the former is converted to a toxic red pigment within the fungus (131,257).…”
Section: Bacterial-fungal Molecular Interactions and Communicationmentioning
confidence: 99%
“…However, practically nothing is known about the sources of melanin precursors in the environment. Recently, we showed that interaction between a bacterium, Klebsiella aerogenes, and C. neoformans resulted in fungal melanization (5). The mechanism for that process involved the production of dopamine by the bacteria that was used as a melanin precursor by C. neoformans.…”
mentioning
confidence: 99%